Problems Faced by University Teachers and Students in the Semester System - Neupane, Ram Nath (Prāgyik Prabāha, 2023)
A semester is a period of six months. This system is very effective in higher education. It is considered more innovative, appropriate, and cooperative than the annual system. It provides the students with an opportunity for continuous learning, assessment, and feedback. However, many teachers and students criticize that they always miss the deadline for course completion so that students cannot engage in extracurricular activities. In this regard, the present study aims to explore the problems faced by university teachers and students in the semester system. To accomplish the objective, the researcher adopted a phenomenological research design under the qualitative method. It is based on the lived experiences of University-level English teachers and students about the semester system at TU. The total population of this study consisted of university EFL teachers and students in Nepal, out of which, the researcher selected only five university EFL teachers and ten students from Tribhuvan multiple campus, Palpa using a purposive sampling procedure. Similarly, the researcher made an interview guideline and then took the interview with the sampled teachers and students to obtain in-depth information. The results revealed that the most of the teachers and students paid more attention to their course contents than to extracurricular activities. Similarly, there are piles of materials in the syllabus; however, most of the important materials are not available in the market. There is no extra facility for economically backward students.